Ants (Hymenoptera: Formicidae) Attracted to Rabbit Carcasses in Three Different Habitats - Ashraf Mashaly; Mostafa R. Sharaf; Medghom al-Subeai; Fahd Al-Mekhlafi; Abdulrahman Aldawood; Gail Anderson (Sociobiology, 2018)
This study reports the ant species that were attracted to rabbit carcasses in three different habitats (agricultural, desert, urban) in the city of Riyadh, Saudi Arabia from May to July 2014. Rabbit carcasses were used as a model for decomposition. Carcasses were categorized as exposed, clothed, shaded and burnt. A total of 726 ants belonging to three subfamilies and 14 species were collected during the decomposition process. Trichomyrmex mayri (Forel) was the only ant species attracted to the carcasses placed in the desert site. At the agricultural site, there was one ponerine species, five formicine species, and three myrmicine species were attracted, while at the urban site, five formicine species and one myrmicine species were recorded. The agricultural site attracted the highest number of ants. In contrast, the desert site attracted the lowest number of ants. Tr. mayri was the most prevalent species occurring in both the agricultural and desert sites. The bloated stage of decomposition attracted the highest number of ants followed by the decay, fresh and dry stages, respectively. Clothed carcasses attracted the highest number of ants followed by the exposed and burnt carcasses, respectively. The shaded carcasses attracted the fewest number of ants. This study found that ants are attracted to carcasses at all stages of decomposition and are common components of the necrofauna of central Saudi Arabia.